CONTOURS OF JURISDICTION UNDER INDIAN ARBITRATION ACT - Pratap, Mayank; Kavita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Arbitration Act, 1940 had no provision which allowed the Arbitral Tribunal to make a decision on its own jurisdiction like Section 16 of the Arbitration and Conciliation Act, 1996 the Arbitral Tribunal has been granted the power to make a ruling on its own jurisdiction. Section 16 (1) of the Arbitration and Conciliation Act states that the Arbitral Tribunal may rule on its own jurisdiction, including ruling on any objection with respect to the existence or validity of the arbitration agreement. The legislative intent underlying the 1996 Act is to minimise judicial intervention in the arbitral process and nominate the arbitrator without wasting time, leaving all contentious issues to be decided by the arbitral tribunal itself Section 16 of the Arbitration and Conciliation Act incorporates the principle of "Compétence-Compétence" or "Compétence de la recognized", is a doctrine that empowers an arbitral tribunal to rule on its own jurisdiction, including ruling on any objection with respect to the existence or validity of the arbitration agreement. It is closely related to rules regarding the allocation of jurisdictional competence between arbitral tribunals and national Courts and to rules concerning the nature and timing of judicial consideration of challenges to an arbitral tribunal’s jurisdiction. The doctrine empowers the arbitrators to decide on their own jurisdiction. The ruling passed in SBP & Co. vs. Patel Engineering Ltd. chipped away the importance of the Kompetenze-Kompetenze principle incorporated in Section 16 consequently, the 2015 Amendment inserted Section 11(6A) in order to restrict the powers of the courts to merely examining the existing of an arbitration agreement. The 2019 Amendment omitted Section 11(6A). now after coming of so many decisions regarding this matter the scope and area of jurisdiction of arbitral tribunal has opened many wings of debate and this chapter is an attempt to discuss all these dimensions